What children need to be happy, confident and successful : step by step positive psychology to help children flourish - Hooper, Jeni (Jennifer Susan), 1952- (London : Jessica Kingsley Publishers, 2012)
Provides a practical model for helping children flourish and achieve their personal potential in every area of their lives. Drawing on ideas from Positive Psychology and child development theory, the model explores the five key areas of wellbeing: personal strengths, emotional wellbeing, positive communication, learning strengths, and resilience. Practical activities are included for each area, and a questionnaire provides an assessment to enable you to keep track of progress. Suitable for use with children aged 3-11, this step-by-step guide is suitable for professionals working with children, including counsellors, social workers, teachers and psychotherapists, as well as parents.--From publisher description.
Includes bibliographical references (p. 171-172) and index.
Keywords: Child psychology; Positive psychology; Child mental health; Child development; Well-being.